2017
DOI: 10.1038/mp.2016.250
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-dependent association of HDAC4 with fear in female mice and women with PTSD

Abstract: Women are at increased risk of developing post-traumatic stress disorder (PTSD) following a traumatic event. Recent studies suggest that this may be mediated, in part, by circulating estrogen levels. This study evaluated the hypothesis that individual variation in response to estrogen levels contributes to fear regulation and PTSD risk in women. We evaluated DNA methylation from blood of female participants in the Grady Trauma Project and found that serum estradiol levels associates with DNA methylation across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 73 publications
2
72
0
Order By: Relevance
“…Complementary to estrogen related transcription factor binding sites being enriched near the PBBassociated CpGs, the effect size for CpGs associated with estradiol levels is correlated with the effect size of those CpGs with PBB, both in the total cohort (R = 0.20, p < 2.2e-16) and in the female participants (N = 381, R = 0.16, p < 2.2e-16. Figure S10) [48]. Additionally, of the 700 PBBassociated CpGs that were also in the estradiol analysis, 211 of them of them were also significantly associated with estradiol.…”
Section: Pbb-associated Cpgs Correlated With Estrogen Signalmentioning
confidence: 91%
See 1 more Smart Citation
“…Complementary to estrogen related transcription factor binding sites being enriched near the PBBassociated CpGs, the effect size for CpGs associated with estradiol levels is correlated with the effect size of those CpGs with PBB, both in the total cohort (R = 0.20, p < 2.2e-16) and in the female participants (N = 381, R = 0.16, p < 2.2e-16. Figure S10) [48]. Additionally, of the 700 PBBassociated CpGs that were also in the estradiol analysis, 211 of them of them were also significantly associated with estradiol.…”
Section: Pbb-associated Cpgs Correlated With Estrogen Signalmentioning
confidence: 91%
“…Because PBB is a known endocrine-disrupting compound and the participants of the Michigan PBB Registry have reported endocrine-related health problems, whether the epigenetic signal from PBB overlapped with the epigenetic signal from estradiol was tested. Enrichment of estradiol associated CpGs was tested using a chi-square test and results from a previously published epigenome-wide study [48]. Because these were identified using data from the Infinium HumanMethylation450 BeadChip, the results from this study were first subset to the probes interrogated by both studies (N = 401,387).…”
Section: Correlations With Estradiol and Immune Signalingmentioning
confidence: 99%
“…MDD, PTSD, and stressful life events have all been associated with changes in DNA methylation (DNAm) . To tease out the role of GC themselves, rodent models of GC exposure have been employed.…”
mentioning
confidence: 99%
“…In contrast to these male-specific findings, a recent study set out to test the hypothesis that individual variation in response to estrogen levels contributes to fear regulation and PTSD risk in women 114 ; this hypothesis is especially notable given the twofold increased risk of PTSD in women compared to men 3 . Drawing again on participants from the Grady Trauma Project, and focusing on genes with demonstrated expression in blood, the investigators identified a single CpG site that associated with PTSD following Bonferroni correction, which fell within the histone deacetylase 4 ( HDAC4 ) gene: methylation was higher in PTSD cases than controls; and higher methylation at this site was associated with lower estradiol levels.…”
Section: Epigenetic Effects Of Stress/trauma Response In the Brain Anmentioning
confidence: 99%
“…Summary of 43 human-based epigenetic studies of PTSD published as of July 2017, enumerated and categorized according to relevant biological system or Epigenome-wide association (EWAS) approach: Hypothalamic-Pituitary Adrenal (HPA) Axis 105,108,116,119,139150 ; EWAS 9196,151155 ; Age-related CpGs 129,132,133 ; Serotonergic system 156,157 ; Neurotrophin 117,158 ; Dopaminergic System 159 ; Catecholaminergic system 102 ; DNA methylation machinery 160 ; Estrogen-responsive genes 114 ; Immune Function 161 ; Other 162165 .…”
Section: Figurementioning
confidence: 99%